Dietary supplementation with fermented plant product modulates production performance, egg quality, intestinal mucosal barrier, and cecal microbiota in laying hens - Tian, Yong; Li, Guoqin; Zhang, Shuo; Zeng, Tao; Chen, Li; Tao, Zhengrong; Lu, Lizhi (Frontiers in Microbiology, 2022)
Fermented plant product (FPP) is a kind of functional complex, containing a variety of bioactive substances, which has many of physiological functions. However, there is no systematic appraisal of FPP as a feed additive for laying hens. This study was conducted to evaluate the utilization of FPP in laying hens. A total of 120 healthy 34-week-old Xianju layers with similar body weight and egg production were randomly divided into 2 dietary treatments with 4 replicates per treatment and 15 birds per replicate for 8 weeks. The dietary treatments included the basal diet without FPP (CON group) and CON diet supplemented with 500 mg/kg of FPP (FPP group). Compared with the CON group, egg production and egg mass were significantly increased in the FPP group from 38 to 42 and 34 to 42 weeks of age (P<0.05). Birds fed dietary containing 500 mg/kg FPP had higher the albumen height (P<0.01) and Haugh unit (P<0.05) than those of the controls. FPP supplementation significantly increased the villus height (VH) and crypt depth (CD) in the jejunum of laying hens (P<0.01), as well as the ratio of VH to CD (P<0.05). The mRNA expression of tight junctions showed that dietary supplemented with FPP significantly increased the expression levels of Occludin (P<0.01) and ZO-1 (P<0.05) in jejunum of hens compared to the control group. In addition, supplemental FPP remodeled cecal microbiota of laying hens, which was characterized by the changes in microbial community composition, incuding the increased adundances of Firmicutes, Faecalibacterium, Oscillospira, Clostridium, Ruminococcus and Coprococcus, along with the decreased abundance of Bacteroidetes, Proteobacteria, Phascolarctobacterium, Odoribacter, Desulfovibrio and Mucispirillum. Spearman’s correlation analysis revealed that Faecalibacterium, Ruminococcus, Coprococcus and Blautia were positively correlated with the intestinal barrier markers. Whereas Desulfovibrio had a negative correlation with the expression of Occludin. Collectively, FPP supplementation increased the egg production, egg mass, albumen height and Haugh unit of laying hens, and improved intestinal health by ameliorating intestinal barrier function, which may be partially attributed to the regulation of cecal microbiota. Our findings suggest that FPP has the potential to be used as feed additive to promote performance of layers.